Journalism and Its Audience - Allaina Kilby (Oxford Research Encyclopedia of Communication, 2019)
The relationship between journalism and its audience has undergone significant transformations from the earliest newspapers in the 18th century to 21st-century digital news. The role of the audience (and journalists’ conceptions of it) has been shaped by economic, social, and technological developments. Though the participation of the audience has always been important to news organizations, it has taken very different forms across times, genres, and platforms. Early newspapers drew on letters from their publics as vital sources of information and opinion, while radio established a more intimate relationship with its audience through its mode of address. Though television news genres may not have emphasized audience engagement, research on the medium was heavily invested in understanding how it affected its audience.The rise of the Internet as a platform for journalism has represented a significant turning point in several respects. First, it has challenged conventional hierarchies of news production and value by facilitating user-generated content and social media, enhancing opportunities for audience contributions. This presents new opportunities for engagement but also challenges journalists’ professional identities, compelling them to assert their authority and skill sets. Further, digital journalism has led to the rise of the quantified audience, leading to the increased role of metrics in driving the behavior of journalists. As the audience and its behavior are shifting, so are the practices of journalism. The two actors—journalists and audiences—remain interlocked in what may be a troubled marriage, but one which is structurally compelled to change and grow over time.